CONTROL OF COTTON PNEUMOTRANSPORT FACILITY THROUGH SCADA SYSTEM - KHOLBAEV, DONIYOR (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article reflects the results of a study of changes in air speed and aerodynamic force on the cross section of the pipe during the transportation of cotton by pneumatic transport. It contains conclusions and proposals for the effective management of the cotton pneumatic conveying process.